2019
DOI: 10.3389/fnhum.2019.00167
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Activity in the Prefrontal Cortex Changes Intertemporal Choice for Loss: A Transcranial Direct Current Stimulation Study

Abstract: Intertemporal choice refers to decisions involving tradeoffs between costs and benefits occurring at different times. Studies have found that weighting the time and benefits during decision-making involves a complex neural network that includes the dorsolateral prefrontal cortex (DLPFC). However, in contrast to literature regarding intertemporal choice for gains, studies have not provided causal evidence that the DLPFC is involved in intertemporal choice for losses. We examined whether bifrontal transcranial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Transcranial direct current stimulation (tDCS) is a non-invasive tool that can reversibly modulate brain activity by applying a weak, constant direct current through the scalp or skull (Nitsche & Paulus, 2000;Dimov et al 2016;Zmigrod et al 2016;Mosayebi Samani et al 2019). Accumulating evidence has demonstrated that polarity-specific tDCS can improve motor performance (Amadi et al 2015;Karok et al 2016), modulate cognitive or perceptual function (Spiegel et al 2012;Spiegel et al 2013;Labbe et al 2016;Price et al 2016;Rosen et al 2016;Weigl et al 2016;Zmigrod et al 2016;Bruckner & Kammer, 2017;Hertenstein et al 2019;Wiegand et al 2019;Xiong et al 2019;Salvi et al 2020), and facilitate learning and memory (Choe et al 2016;Sandrini et al 2016;Van Meel et al 2016;Ke et al 2019;Nissim et al 2019;Gibson et al 2020). Clinical studies showed that tDCS is a potential therapeutic tool for some neurological or psychiatric disorders (Yoon et al 2012;Zobeiri & van Luijtelaar, 2013;Assenza et al 2014;Dhamne et al 2015;Ding et al 2016;Kang et al 2019;Strumila et al 2019;Vigod et al 2019;Cosentino et al 2020;McClintock et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Transcranial direct current stimulation (tDCS) is a non-invasive tool that can reversibly modulate brain activity by applying a weak, constant direct current through the scalp or skull (Nitsche & Paulus, 2000;Dimov et al 2016;Zmigrod et al 2016;Mosayebi Samani et al 2019). Accumulating evidence has demonstrated that polarity-specific tDCS can improve motor performance (Amadi et al 2015;Karok et al 2016), modulate cognitive or perceptual function (Spiegel et al 2012;Spiegel et al 2013;Labbe et al 2016;Price et al 2016;Rosen et al 2016;Weigl et al 2016;Zmigrod et al 2016;Bruckner & Kammer, 2017;Hertenstein et al 2019;Wiegand et al 2019;Xiong et al 2019;Salvi et al 2020), and facilitate learning and memory (Choe et al 2016;Sandrini et al 2016;Van Meel et al 2016;Ke et al 2019;Nissim et al 2019;Gibson et al 2020). Clinical studies showed that tDCS is a potential therapeutic tool for some neurological or psychiatric disorders (Yoon et al 2012;Zobeiri & van Luijtelaar, 2013;Assenza et al 2014;Dhamne et al 2015;Ding et al 2016;Kang et al 2019;Strumila et al 2019;Vigod et al 2019;Cosentino et al 2020;McClintock et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The scalp region overlying the dmPFC was located by measuring 15% of the distance from the Fz to the FPz ( Martin et al, 2019 ). In accordance with previous studies, the reference electrode was placed over the arm ( Xiong et al, 2019 ). The rTPJ was located at CP6 electrode site according to the international electroencephalography (EEG) 10–20 system.…”
Section: Methodsmentioning
confidence: 98%
“…The stimulation was administered using a one-channel direct current stimulator (DC-STIMULATOR; neuroConn, Ilmenau, Germany) and saline-soaked surface sponge electrodes (5 × 7 cm; Xiong et al, 2019 ). The FPz and Fz electrode sites were first measured and identified for each participant.…”
Section: Methodsmentioning
confidence: 99%
“…In the past two decades, >1,000 articles have been published in which tDCS tools are used (e.g., Jantz et al, 2016 ; Xiong et al, 2019 ). A simple, painless, and noninvasive technique is used for the modulation of brain activity, with a low-intensity direct current applied.…”
Section: Methodsmentioning
confidence: 99%